Criminal macabre omnibus, volume 2 ebook - Niles, Steve (Criminal Macabre (2003), 2011)
Cal McDonald, the pillpopping, alcoholic antihero of the hit Criminal Macabre series, is back! Teamed with his undead partner Mo'Lock, Cal protects the sininfested streets of Los Angeles against a growing horde of zombies, vampires, and occultists!This trade collects Criminal Macabre Volumes 46, the oneshot story Feat of Clay, ""The Creepy Tree"" and ""The Trouble with Brains"" from MySpace Dark Horse Presents, and ""Hairball"" from Dark Horse Presents #102#105, featured in color for the first time!* From the creator of 30 Days of Night.""I literally screamed HOLY $#@% when I put this book down. It is that good... Cal McDonald is truly one of the coolest characters in comics.""Ain't it Cool News